Studies on the Immunity to Eimeria tenella in Chickens: I. The Changes in Number of Parasites in Caecal Tissue and the Relation between Circulating Antibody and Resistance to Infection in Immune Chickens - OKAMOTO, Seikan; TOJO, Hideaki (Japanese poultry science, 1971)
The experiment reported here were designed to investigate the changes in number of the parasite in the caecal tissue of immune chicken with Eimeria tenella as the infection progressed in time and to determine the immunizing effect on resistance to infection after injection of parasites extract (schizont antigen). Male commercial White Leghorn chickens fed a ration containing no antibiotics or coccidiostats were used. The results are summarized as follows. I. There were fewer parasites in the caecal tissue of the immune chicken than in the non-immune chicken. However, the difference in number of the parasite between the two groups was negligible up to 24 hours after challenge infection but the development of parasites in the immune chicken markedly decreased after 72 or 96 hours of the infection as compared to the non-immune chicken. II. The sera from the immune chickens subjected to the injection of schizont antigen showed appreciable agglutination or lytic effect on merozoites, whereas these chickens were apparently more susceptible to challenge infection than the immune chickens after the oral infection with oocysts, determined by the number of discharged oocysts. Accordingly, these results suggested that the circulating antibody was not essential for the immunity to coccidia.